2020
DOI: 10.1186/s12893-020-00957-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different types of cerebral perfusion for acute type A aortic dissection undergoing aortic arch procedure, unilateral versus bilateral

Abstract: Background Antegrade cerebral perfusion (ACP), including unilateral and bilateral, is most commonly used for cerebral protection in aortic surgery. There is still no consensus on the superiority of the two methods. Our research aimed to investigate the clinical effects of u-ACP and b-ACP. Methods 321 of 356 patients with type A aortic dissection were studied retrospectively. 124 patients (38.6%) received u-ACP, and 197 patients (61.4%) received b-ACP. We compared the incidence of postoperative neurological co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Detailed study selection process is presented inSupplemental Figure 1 . Ultimately, 8 studies reporting on cumulatively 2416 patients, 843 patients undergoing UACP and 1573 patients undergoing BACP were included in this metaanalysis 6,7,[16][17][18][19][20][21] . Study characteristics are reported in Table 1 .…”
Section: Study Selection and Baseline Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed study selection process is presented inSupplemental Figure 1 . Ultimately, 8 studies reporting on cumulatively 2416 patients, 843 patients undergoing UACP and 1573 patients undergoing BACP were included in this metaanalysis 6,7,[16][17][18][19][20][21] . Study characteristics are reported in Table 1 .…”
Section: Study Selection and Baseline Characteristicsmentioning
confidence: 99%
“…ICU stay duration was reported in five studies 7,16,17,19,20 . UACP demonstrated increased ICU stay length compared to BACP (SMD: 0.16, 95%CI: [0.01] -[0.31], p =0.04, I 2 =28.56%).…”
Section: Icu Staymentioning
confidence: 99%
See 3 more Smart Citations